Preparation method of diaphragm material based on solid electrolyte

Through the mixed slurry preparation process of phosphate glass, LiFePO4 positive electrode material and conductive carbon black, the problems of poor conductivity and low thermal stability of solid electrolyte separator materials are solved, which significantly improves the conductivity and structural stability and improves the lithium battery. Energy density and safety performance.

CN119153765APending Publication Date: 2024-12-17ZHONGCHEN JICHI (GANSU) NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411029155.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The poor conductivity and low thermal stability of existing solid electrolyte separators limit the energy density and safety performance of lithium batteries.

Method used

A mixed slurry of phosphate glass, LiFePO4 positive electrode material and conductive carbon black was dried, pressed and sintered at high temperature to prepare a uniform solid electrolyte membrane, and was subjected to scanning electron microscope, energy dispersion X-ray spectrometer, thermogravimetric analyzer and Electrochemical workstations are characterized and the preparation process is optimized to improve material performance.

Benefits of technology

It significantly improves the conductivity and structural stability of the solid electrolyte separator, improves the problems of poor conductivity and low thermal stability, and improves the energy density and safety performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153765A_ABST
    Figure CN119153765A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery diaphragm materials, and discloses a preparation method based on a solid electrolyte diaphragm material, which comprises the following steps: S1, preparing a solid electrolyte material: grinding phosphate glass into powder; and S2, preparing mixed slurry: mixing the Li FePO4 positive electrode material, phosphate glass and conductive carbon black. According to the preparation method based on the solid electrolyte diaphragm material, phosphate glass has good ion conduction performance and relatively high thermal stability, and in the preparation process of mixed slurry of the Li FePO4 positive electrode material, the phosphate glass and conductive carbon black, the conductivity and the structural stability of the solid electrolyte diaphragm can be improved by controlling the mass ratio and mixing; and then the dried mixed particles are put into a high-temperature sintering furnace to be sintered, and then the uniform solid electrolyte diaphragm is prepared, so that the performance of the solid electrolyte diaphragm can be effectively improved, and the problems of poor conductivity, low thermal stability and the like existing in an existing solid electrolyte diaphragm material are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery diaphragm materials, and in particular to a preparation method based on a solid electrolyte diaphragm material. Background Art

[0002] As people's requirements for the energy density and safety performance of lithium batteries are increasing, solid-state lithium batteries will become the first choice for the new generation of high energy density and high safety batteries. One of the key technologies in solid-state batteries is solid electrolyte diaphragm technology. The quality of the diaphragm directly affects the battery's energy density, safety, rate performance, and high and low temperature performance.

[0003] Battery separator materials are usually a thin film used to isolate the positive and negative electrodes of the battery to prevent them from direct contact and causing a short circuit. Separator materials play an important role in batteries. They need to have certain properties, such as electrolyte permeability, ion conductivity, chemical stability and mechanical strength. With the advancement of science and technology, new separator materials are also being continuously developed and applied to improve battery performance and safety. The commonly used solid electrolyte separator materials currently include polymers, inorganic oxides and sulfides. These materials have certain limitations in practical applications, such as poor conductivity and low thermal stability. Therefore, it is necessary to find more suitable materials to improve the performance of solid electrolyte separators. Therefore, we propose a preparation method based on solid electrolyte separator materials. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the shortcomings of the prior art, the present invention provides a preparation method based on a solid electrolyte membrane material, which has the advantage of effectively improving the performance of the solid electrolyte membrane, and solves the problem that the currently commonly used solid electrolyte membrane materials mainly include polymers, inorganic oxides and sulfides, etc. These materials have certain limitations in practical applications, such as poor conductivity and low thermal stability. Therefore, it is necessary to find more suitable materials to improve the performance of the solid electrolyte membrane.

[0006] (II) Technical solution

[0007] In order to achieve the above-mentioned purpose of effectively improving the performance of the solid electrolyte membrane, the present invention provides the following technical solutions:

[0008] A method for preparing a solid electrolyte diaphragm material comprises the following steps:

[0009] S1. Prepare solid electrolyte material: grind phosphate glass into powder;

[0010] S2, preparing a mixed slurry: mixing LiFePO4 positive electrode material, phosphate glass and conductive carbon black;

[0011] S3, drying the mixed slurry: taking out the mixed slurry, using a drying furnace to remove the solvent therein, and obtaining dry mixed particles;

[0012] S4, pressing: placing the dried mixed granules into a mold and pressing;

[0013] S5, high temperature sintering: placing the pressed membrane material into a high temperature sintering furnace for sintering to prepare a uniform solid electrolyte membrane;

[0014] S6. Characterization and analysis: Characterize the structure and composition of the prepared solid electrolyte membrane material.

[0015] Preferably, the phosphate glass is ground and pulverized by a grinder, and sieved by a screening machine to ensure that the particle size of the phosphate glass powder is within the range of 1-10 microns.

[0016] Preferably, the mass ratio of LiFePO4 positive electrode material, phosphate glass and conductive carbon black is 50:40:10.

[0017] Preferably, the drying temperature of the drying furnace is set between 100-150° C., and the mixed slurry is dried continuously for 2-4 hours.

[0018] Preferably, during the pressing process of the dried mixed particles, the pressing temperature of the mold is controlled between 100-150° C., and the pressure is controlled within the range of 50-100 MPa.

[0019] Preferably, the sintering temperature of the membrane material in the high-temperature sintering furnace is controlled between 700-900° C., and the sintering time is 1-4 hours.

[0020] Preferably, the structure and composition of the solid electrolyte membrane material are characterized by a scanning electron microscope, an energy dispersive X-ray spectrometer, a thermogravimetric analyzer and an electrochemical workstation. The specific process is as follows:

[0021] S61, cutting a representative sample from the prepared solid electrolyte separator material, and grinding and polishing the sample to obtain a smooth surface;

[0022] S62, fixing the sample on the sample holder of the scanning electron microscope, and performing gold spraying to improve the conductivity of the sample, setting the working distance and the accelerating voltage, and performing high-resolution scanning observation on the sample to obtain the microscopic morphology and particle size distribution information of the diaphragm material;

[0023] S63, placing the sample under the probe of the energy dispersive X-ray spectrometer, determining the elemental composition and distribution of the sample by exciting the X-ray source and detecting the characteristic X-rays scattered by the sample, collecting energy spectrum data of different regions, and performing quantitative analysis and comparison;

[0024] S64, placing the membrane material sample in a thermogravimetric analyzer, heating it to different temperature ranges at a certain heating rate, recording the mass change of the sample with temperature, and evaluating its thermal stability and possible decomposition temperature;

[0025] S65, using an electrochemical workstation to test the electrochemical performance of the diaphragm material sample, making the sample into an electrode sheet, and assembling it into a battery together with a reference electrode and an auxiliary electrode, and measuring the parameters of the diaphragm material sample by cyclic voltammetry;

[0026] S66. Based on the experimental results, the morphology, composition, thermal stability and electrochemical properties of the diaphragm materials are analyzed and compared, experimental conclusions are drawn, and suggestions for optimizing and improving the preparation process are made.

[0027] Preferably, the parameters of the membrane material sample include ionic conductivity, capacitance and electrochemical window.

[0028] (III) Beneficial effects

[0029] Compared with the prior art, the present invention provides a preparation method based on solid electrolyte diaphragm material, which has the following beneficial effects:

[0030] 1. The preparation method based on the solid electrolyte membrane material grinds phosphate glass into powder and screens it with a screening machine. The phosphate glass has good ion conductivity and high thermal stability. In the preparation process of the mixed slurry of LiFePO4 positive electrode material, phosphate glass and conductive carbon black, reasonable mass ratio control is performed to uniformly mix them, which can improve the electrical conductivity and structural stability of the solid electrolyte membrane. The dried mixed particles are then placed in a high-temperature sintering furnace for sintering treatment, thereby preparing a uniform solid electrolyte membrane, which can effectively improve the performance of the solid electrolyte membrane and greatly improve the existing solid electrolyte membrane materials. Problems such as poor conductivity and low thermal stability.

[0031] 2. The preparation method based on solid electrolyte membrane material characterizes the structure and components of the prepared solid electrolyte membrane material, including scanning electron microscope observation of microscopic morphology and particle size distribution information, energy dispersive X-ray spectrometer analysis of elemental composition and distribution, thermogravimetric analyzer evaluation of thermal stability and decomposition temperature, electrochemical workstation testing of electrochemical performance, etc. These characterization methods can fully understand the morphology, composition, thermal stability and electrochemical performance of the membrane material, and provide a basis for further optimization and improvement of the preparation process. By optimizing and improving the preparation process, the performance of the solid electrolyte membrane can be improved, thereby solving the limitations of existing materials in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the preparation process of the solid electrolyte membrane material of the present invention;

[0033] Figure 2 It is a schematic diagram of the characterization process of the structure and components of the solid electrolyte membrane material of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention and the accompanying drawings to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] See also Figure 1-2 , a preparation method based on a solid electrolyte membrane material, comprising the following steps:

[0036] S1. Prepare solid electrolyte material: grind phosphate glass into powder;

[0037] S2, preparing a mixed slurry: mixing LiFePO4 positive electrode material, phosphate glass and conductive carbon black;

[0038] S3, drying the mixed slurry: taking out the mixed slurry, using a drying furnace to remove the solvent therein, and obtaining dry mixed particles;

[0039] S4, pressing: placing the dried mixed granules into a mold and pressing;

[0040] S5, high temperature sintering: placing the pressed membrane material into a high temperature sintering furnace for sintering to prepare a uniform solid electrolyte membrane;

[0041] S6. Characterization and analysis: Characterize the structure and composition of the prepared solid electrolyte membrane material.

[0042] Specifically, the phosphate glass is ground and crushed by a grinder, and screened by a screening machine to ensure that the particle size of the phosphate glass powder is within the range of 1-10 microns.

[0043] Furthermore, controlling the particle size within the range of 1-10 microns can provide certain advantages. Small-particle phosphate glass powder has a larger specific surface area, which is beneficial to the reactivity and ion transport performance of the material. Moreover, the uniformity of the particle size distribution can improve the uniformity and stability of the material. Therefore, the purpose of this step is to obtain phosphate glass powder with an appropriate particle size to improve the performance of the prepared solid electrolyte membrane material.

[0044] Specifically, the mass ratio between the LiFePO4 positive electrode material, the phosphate glass and the conductive carbon black is 50:40:10.

[0045] Furthermore, LiFePO4 positive electrode material has good electrochemical properties in lithium-ion batteries, phosphate glass is an important component of solid electrolyte, and conductive carbon black can improve the conductivity of the material. By mixing them in a mass ratio of 50:40:10, a suitable ratio of positive electrode material, electrolyte and conductive carbon black can be obtained in the solid electrolyte separator material, thereby optimizing the material's ion conductivity, electrochemical window and capacity characteristics.

[0046] Specifically, the drying temperature of the drying furnace is set between 100-150° C., and the mixed slurry is dried continuously for 2-4 hours.

[0047] Furthermore, by placing the mixed slurry into a drying furnace and drying it at a temperature range of 100-150°C, the solvent therein can be effectively evaporated and removed, which can ensure that the solid particles in the mixture can combine with each other and form a uniform mixture. At the same time, the duration of the drying process can control the moisture level of the mixture to achieve the desired degree of dryness.

[0048] Specifically, during the pressing process of the dry mixed particles, the pressing temperature of the mold is controlled between 100-150° C., and the pressure is controlled within the range of 50-100 MPa.

[0049] Furthermore, by controlling the temperature and pressure of the mold during the pressing process, the contact between the particles of the mixture can be made closer, promoting the bonding and sintering between the particles, thus ensuring that the structure and components of the solid electrolyte membrane material are evenly distributed and have high mechanical strength and stability. In addition, appropriate pressing temperature and pressure can also promote the chemical reaction of the phosphate glass and LiFePO4 positive electrode material in the mixture, further improving the ion conductivity and electrochemical stability of the solid electrolyte membrane material, which is of great significance for the preparation of high-performance solid electrolyte membrane materials.

[0050] Specifically, the sintering temperature of the membrane material in the high-temperature sintering furnace is controlled between 700-900° C., and the sintering time is 1-4 hours.

[0051] Furthermore, by controlling the sintering temperature and time, the phosphate glass and LiFePO4 positive electrode material in the mixture can undergo a chemical reaction to generate a solid electrolyte membrane with good ion conductivity and stability. In addition, the residual solvent in the mixed slurry can be removed during the sintering process, further improving the purity and quality of the membrane material.

[0052] Specifically, the structure and composition of the solid electrolyte membrane material are characterized by scanning electron microscopy, energy dispersive X-ray spectrometer, thermogravimetric analyzer and electrochemical workstation. The specific process is as follows:

[0053] S61, cutting a representative sample from the prepared solid electrolyte separator material, and grinding and polishing the sample to obtain a smooth surface;

[0054] S62, fixing the sample on the sample holder of the scanning electron microscope, and performing gold spraying to improve the conductivity of the sample, setting the working distance and the accelerating voltage, and performing high-resolution scanning observation on the sample to obtain the microscopic morphology and particle size distribution information of the diaphragm material;

[0055] S63, placing the sample under the probe of the energy dispersive X-ray spectrometer, determining the elemental composition and distribution of the sample by exciting the X-ray source and detecting the characteristic X-rays scattered by the sample, collecting energy spectrum data of different regions, and performing quantitative analysis and comparison;

[0056] S64, placing the membrane material sample in a thermogravimetric analyzer, heating it to different temperature ranges at a certain heating rate, recording the mass change of the sample with temperature, and evaluating its thermal stability and possible decomposition temperature;

[0057] S65, using an electrochemical workstation to test the electrochemical performance of the diaphragm material sample, making the sample into an electrode sheet, and assembling it into a battery together with a reference electrode and an auxiliary electrode, and measuring the parameters of the diaphragm material sample by cyclic voltammetry;

[0058] S66. Based on the experimental results, the morphology, composition, thermal stability and electrochemical properties of the diaphragm materials are analyzed and compared, experimental conclusions are drawn, and suggestions for optimizing and improving the preparation process are made.

[0059] Furthermore, a scanning electron microscope can provide high-resolution images of diaphragm materials to help observe the microscopic morphology and particle size distribution of diaphragm materials; an energy dispersive X-ray spectrometer can determine the elemental composition and distribution of samples by exciting an X-ray source and detecting characteristic X-rays scattered by the sample, collect energy spectrum data from different regions, and perform quantitative analysis and comparison; a thermogravimetric analyzer can heat samples to different temperature ranges at a certain heating rate, record the changes in the mass of the samples with temperature, and evaluate their thermal stability and possible decomposition temperature; an electrochemical workstation can perform electrochemical performance tests on diaphragm material samples, make the samples into electrode sheets, and assemble them into batteries together with reference electrodes and auxiliary electrodes, and measure the parameters of diaphragm material samples by cyclic voltammetry.

[0060] Specifically, the parameters of the membrane material samples include ionic conductivity, capacitance and electrochemical window.

[0061] Furthermore, ions determine the size of the battery's internal resistance and have an important impact on the battery's energy density and power density. By measuring the ionic conductivity of the diaphragm material, its conductive performance can be evaluated. The capacitance is closely related to the battery's energy density. By measuring the capacitance of the diaphragm material, its energy storage performance can be evaluated. The electrochemical window determines the battery's operating voltage window. By measuring the electrochemical window of the diaphragm material, its stability and safety can be evaluated. By testing and analyzing the ionic conductivity, capacitance and electrochemical window of diaphragm material samples, experimental conclusions can be drawn, and suggestions for optimization and improvement of the preparation process can be made, which will help improve the quality and performance of solid electrolyte diaphragm materials and further promote their application in energy storage and conversion.

[0062] In summary, the preparation method based on the solid electrolyte membrane material grinds the phosphate glass into powder and screens it with a screening machine. The phosphate glass has good ion conductivity and high thermal stability. In the preparation process of the mixed slurry of LiFePO4 positive electrode material, phosphate glass and conductive carbon black, reasonable mass ratio control is performed to uniformly mix them, which can improve the electrical conductivity and structural stability of the solid electrolyte membrane. The dried mixed particles are then placed in a high-temperature sintering furnace for sintering treatment, thereby preparing a uniform solid electrolyte membrane, which can effectively improve the performance of the solid electrolyte membrane and greatly improve the existing solid electrolyte membrane materials. Problems such as poor conductivity and low thermal stability.

[0063] In addition, the preparation method based on the solid electrolyte diaphragm material characterizes the structure and components of the prepared solid electrolyte diaphragm material, including scanning electron microscope observation of microscopic morphology and particle size distribution information, energy dispersive X-ray spectrometer analysis of elemental composition and distribution, thermogravimetric analyzer evaluation of thermal stability and decomposition temperature, electrochemical workstation testing of electrochemical performance, etc. These characterization methods can fully understand the morphology, composition, thermal stability and electrochemical performance of the diaphragm material, and provide a basis for further optimization and improvement of the preparation process. By optimizing and improving the preparation process, the performance of the solid electrolyte diaphragm can be improved, thereby solving the limitations of existing materials in practical applications. The commonly used solid electrolyte diaphragm materials currently include polymers, inorganic oxides and sulfides, etc. These materials have certain limitations in practical applications, such as poor conductivity, low thermal stability and other problems. Therefore, it is necessary to find more suitable materials to improve the performance of the solid electrolyte diaphragm.

[0064] The relevant modules involved in this system are all hardware system modules or functional modules that combine computer software programs or protocols with hardware in the prior art. The computer software programs or protocols involved in the functional modules are themselves technologies that are well known to those skilled in the art and are not improvements of this system. The improvements of this system are the interaction or connection relationships between the modules, that is, improvements to the overall structure of the system to solve the corresponding technical problems to be solved by this system.

[0065] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A preparation method based on a solid electrolyte diaphragm material, characterized in that: The following steps are involved: S1. Prepare solid electrolyte material: grind phosphate glass into powder; S2. preparing a mixed slurry: mixing LiFePO4 positive electrode material, phosphate glass and conductive carbon black; S3, drying the mixed slurry: taking out the mixed slurry, using a drying furnace to remove the solvent therein, and obtaining dry mixed particles; S4, pressing: placing the dried mixed granules into a mold and pressing; S5, high temperature sintering: placing the pressed membrane material into a high temperature sintering furnace for sintering to prepare a uniform solid electrolyte membrane; S6. Characterization and analysis: Characterize the structure and composition of the prepared solid electrolyte membrane material.

2. A method for preparing a solid electrolyte membrane material according to claim 1, characterized in that: In S1, the phosphate glass is ground and pulverized by a grinder, and sieved by a screening machine to ensure that the particle size of the phosphate glass powder is within the range of 1-10 microns.

3. The method for preparing a solid electrolyte diaphragm material according to claim 1, characterized in that: In the S2, the mass ratio of LiFePO4 positive electrode material, phosphate glass and conductive carbon black is 50:40:

10.

4. The method for preparing a solid electrolyte diaphragm material according to claim 1, characterized in that: In S3, the drying temperature of the drying furnace is set between 100-150° C., and the mixed slurry is dried continuously for 2-4 hours.

5. The method for preparing a solid electrolyte membrane material according to claim 1, characterized in that: In S4, during the pressing process of the dried mixed particles, the pressing temperature of the mold is controlled between 100-150° C., and the pressure is controlled within the range of 50-100 MPa.

6. The method for preparing a solid electrolyte membrane material according to claim 1, characterized in that: In S5, the sintering temperature of the membrane material in the high-temperature sintering furnace is controlled between 700-900° C., and the sintering time is 1-4 hours.

7. The method for preparing a solid electrolyte diaphragm material according to claim 1, characterized in that: In S6, the structure and components of the solid electrolyte membrane material are characterized by a scanning electron microscope, an energy dispersive X-ray spectrometer, a thermogravimetric analyzer and an electrochemical workstation. The specific process is as follows: S61, cutting a representative sample from the prepared solid electrolyte separator material, and grinding and polishing the sample to obtain a smooth surface; S62, fixing the sample on the sample holder of the scanning electron microscope, and performing gold spraying to improve the conductivity of the sample, setting the working distance and the accelerating voltage, and performing high-resolution scanning observation on the sample to obtain the microscopic morphology and particle size distribution information of the diaphragm material; S63, placing the sample under the probe of the energy dispersive X-ray spectrometer, determining the elemental composition and distribution of the sample by exciting the X-ray source and detecting the characteristic X-rays scattered by the sample, collecting energy spectrum data of different regions, and performing quantitative analysis and comparison; S64, placing the membrane material sample in a thermogravimetric analyzer, heating it to different temperature ranges at a certain heating rate, recording the mass change of the sample with temperature, and evaluating its thermal stability and possible decomposition temperature; S65, using an electrochemical workstation to test the electrochemical performance of the diaphragm material sample, making the sample into an electrode sheet, and assembling it into a battery together with a reference electrode and an auxiliary electrode, and measuring the parameters of the diaphragm material sample by cyclic voltammetry; S66. Based on the experimental results, the morphology, composition, thermal stability and electrochemical properties of the diaphragm materials are analyzed and compared, experimental conclusions are drawn, and suggestions for optimizing and improving the preparation process are made.

8. A method for preparing a solid electrolyte diaphragm material according to claim 7, characterized in that: In the above S65, the parameters of the membrane material sample include ionic conductivity, capacitance and electrochemical window.